2016
DOI: 10.1016/j.ajhg.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic Activating Mutations in FGFR1 Cause Encephalocraniocutaneous Lipomatosis

Abstract: Encephalocraniocutaneous lipomatosis (ECCL) is a sporadic condition characterized by ocular, cutaneous, and central nervous system anomalies. Key clinical features include a well-demarcated hairless fatty nevus on the scalp, benign ocular tumors, and central nervous system lipomas. Seizures, spasticity, and intellectual disability can be present, although affected individuals without seizures and with normal intellect have also been reported. Given the patchy and asymmetric nature of the malformations, ECCL ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 62 publications
5
64
1
Order By: Relevance
“…Our data in NOF add another benign tumour to the spectrum of KRAS ‐ and MAP‐kinase signalling‐driven neoplasms, by identifying bona fide pathogenic KRAS and FGFR1 mutations that have been reported in a variety of carcinomas, sarcomas and haematological malignancies. Interestingly, FGFR1 mutations have recently been shown to occur in (sporadic) phaeochromocytomas (that can also harbour NF1 mutations), and in rare brain tumour subtypes .…”
Section: Discussionmentioning
confidence: 99%
“…Our data in NOF add another benign tumour to the spectrum of KRAS ‐ and MAP‐kinase signalling‐driven neoplasms, by identifying bona fide pathogenic KRAS and FGFR1 mutations that have been reported in a variety of carcinomas, sarcomas and haematological malignancies. Interestingly, FGFR1 mutations have recently been shown to occur in (sporadic) phaeochromocytomas (that can also harbour NF1 mutations), and in rare brain tumour subtypes .…”
Section: Discussionmentioning
confidence: 99%
“…These entities are the oculoectodermal (OES, OMIM %600268) and Schimmelpenning‐Feuerstein‐Mims syndromes (SFMS, OMIM #163200), as well as encephalocraniocutaneous lipomatosis (ECCL, OMIM #613001), oculocutaneous disorders exhibiting pleiotropic anomalies that include scalp lesions, epilepsy, epibulbar dermoids, cloudy cornea, eyelid coloboma, coarctation of the aorta, and skin pigmentation abnormalities (Boppudi et al, ; Groesser et al, ; Kuroda et al, ; Peacock et al, ). Somatic mutations causing oculocutaneous mosaic RASopathies are recurrent and have been identified at KRAS codons 13, 19, and 146 in OES patients (4 subjects reported to date) (Boppudi et al, ; Peacock et al, ), KRAS codon 146 and FGFR1 codons 546 and 656 in ECCL (six reported patients) (Bennett et al, ; Boppudi et al, ), and HRAS codon 13 (2 patients), KRAS codon 12 (3 subjects), and NRAS codon 61 (1 subject) in individuals with a SFMS diagnosis (Groesser et al, ; Igawa et al, ; Kuroda et al, ; Lihua, Feng, Shanshan, Jialu, & Kewen, ; Sun et al, ; Wang, Qian, Zhang, & Zhou, ). Such pathogenic mutations also confer an elevated risk for developing a variety of tumors commonly associated with these oculocutaneos disorders (Aslan et al, ; Eisen & Michael; ; Kocak, Yarar, & Carman, ; Moog, ; Peacock et al, ; Toriello et al, ; Valera et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study the mosaic activating mutations of fibroblast growth factor receptor gene‐1 ( FGFR1 ) were found to be related to ECCL . In the present patient, no mutations were detected in FGFR or WT1 on Sanger analysis of the peripheral blood.…”
Section: Discussionmentioning
confidence: 45%